Wavelet-based semblance analysis to determine muscle synergy for different handstand postures of Chilean circus athletes. Issue 10 (7th September 2021) - Calderón-Díaz, Mailyn; Ulloa-Jiménez, Ricardo; Saavedra, Carolina; Salas, Rodrigo
Abstract: The handstand is an uncommon posture, highly demanding in terms of muscle and joint stability, used in sporting and artistic practices in a variety of disciplines. Despite its becoming increasingly widespread, there is no specific way to perform a handstand, and the neuromuscular organizational mechanisms involved are unknown. The objective of this study was to determine the muscle synergy of four handstand postures through a semblance analysis based on wavelets of electromyographic signals in the upper limbs of experienced circus performers between 18- and 35-year old. The results show that there is a large difference in positive and negative correlations depending on the posture, which suggests that the more asymmetrical the position of the lower limbs, the greater the number of strategies to maintain the posture. Although it is not a statistically significant data, it is observed that the posture 3 in particular, possesses the greatest number of positive correlations, which suggests it has the greatest synergy.